Handbook of conflict analysis and resolution - Sandole, Dennis J. D. (London ; New York : Routledge, 2009)
This handbook is a collection of works from leading scholars in the conflict analysis and resolution field, all working from their own disciplines yet cognizant of the multidisciplinary nature of that field.
Core practices : processes -- Conflict transformation : reasons to be modest / Stephen Ryan -- Mediation frames/justice games / Andrew Woolford, R. S. Ratner --Interactive conflict resolution : dialogue, conflict analysis, and problemsolving / Ronald J. Fisher -- Mediation and international conflict resolution : analyzing structure and behavior / Jacob Bercovitch -- Ethical and gendered dilemmas of moving from emergency response to development in "failed" states / Janie Leatherman, Nadezhda Griffin (formerly Negrustueva) -- Memory retrieval and truth recovery / Paul Arthur -- Shifting from coherent toward holistic peace processes / Susan Allen Nan -- Law and legal processes in resolving international conflicts / Michelle Gallant -- Alternative voices and complex intervention designs -- Restorative processes of peace and healing within the governing structures of the Rotinonshonni "Longhouse People" / Brian Rice -- Critical systematic inquiry in conflict analysis and resolution : an essential bridge between theory and practice / Dennis J. D. Sandole -- From diagnosis to treatment : toward new shared principles for Israeli-Palestinian peacebuilding / Walid Salem, Edy Kaufman -- Strategies for the prevention, management, and/or resolution of (ethnic) crisis and conflict : the case of the Balkans / Mitja Žagar -- The perception of economic assistance in Northern Ireland and its role in the peace process / Sean Byrne, Cynthia Irvin, Eyob Fissuh -- Conflict resolution in an age of empire : new challenges to an emerging field / Richard E. Rubenstein -- Conclusions -- Toward a conflictology : the quest for transdisciplinarity / Johan Galtung-- Revisiting the CAR field / Sean Byrne, Jessica Senehi -- Epilogue : implications for theory, research, practice, and teaching / Dennis J. D. Sandole, Ingrid Sandole-Staroste.
Bibliografske bilješke uz svaki rad
Kazalo
Keywords: sukob; sociologija sukoba; rješavanje sukoba; međusobni sukobi; unutargrupni sukobi; organizacijski sukobi; međunarodni sukobi